Investigation On The Performance Of Biosorbent And Activated Carbon In The Removal Of Cationic Contaminant From Water - Kayshni, Lingeswaran (2020)
Nickel ions which are commonly found in the wastewater discharge of a variety of industries pose serious threats to ecosystems and human health if their concentrations exceed permissible limits. Activated carbon adsorption is typically employed in the treatment of wastewater to remove heavy metal contaminants such as nickel from water. However, the cost of activated carbon itself is high. Longan peel was proposed as a low-cost biosorbent substitute to activated carbon. The present study focuses on investigating and comparing the efficiency of both these adsorbents in removing nickel (II) ions from aqueous solutions. Operating parameters which are initial nickel concentration, adsorbent dosage, and pH were examined to analyse the effects that they have on the removal of nickel ions. Based on Box-Behnken design of experiments, reduced cubic models were proposed to correlate the three independent variables for maximum removal efficiencies at optimum conditions. The maximum removal efficiency of nickel (II) by longan peel biosorbent was determined to be 47.64 % at optimal parameters: initial nickel concentration of 180.17 mg/L, biosorbent dosage of 9.708g, and pH 5.346. Optimal conditions for activated carbon were found to be initial nickel concentration of 11.94 mg/L, biosorbent dosage of 7.585 g, and pH 7.999, which resulted in a maximum removal efficiency of 97.85 %. Langmuir isotherm and Freundlich isotherm models exhibited the best fits for the equilibrium data for longan peel and activated carbon respectively. Despite the potential that longan peel biosorbent has shown in removing nickel ions from contaminated water, its performance pales in comparison to activated carbon and other low-cost biosorbents. Several suggestions were made to help overcome the shortcomings that the longan peel biosorbent has in terms of its adsorption capacity. In addition, recommendations for future research related to increasing the feasibility of adopting longan peel biosorbent in actual wastewater treatment plants were also presented.